Functional epitopes on hepatitis E virions and recombinant capsids are highly conformation-dependent - Bin He; Zhigang Zhang; Xinyuan Zhang; Zimin Tang; Chang Liu; Zizheng Zheng; Shaowei Li; Jun Zhang; Ningshao Xia; Qinjian Zhao (Taylor & Francis Group, 2020)
Hepatitis E virus (HEV) is responsible for epidemic and sporadic acute hepatitis cases, especially in developing countries. Hepatitis E has become a vaccine-preventable disease in recent years with the development of a licensed vaccine. Most functional and neutralizing monoclonal antibodies (mAbs) are known to be highly sensitive to antigen conformation. In this study, a similar approach was used to characterize the conformational sensitivity of antibodies in human or mouse serum samples. Interestingly, comparative binding analysis using different antigen forms showed that the antibodies in the sera of naturally infected individuals, of human vaccinees and from mice immunized with the HEV p239 vaccine all exhibited a strong preference to particulate antigens over the monomeric form of the truncated capsid protein. The degree of discriminating the two test antigens is similar for serum samples to that for the well-characterized murine mAbs. A functional assay for assessing the inhibition of subviral particle cell entry by antibodies was used to determine the functional titers of anti-HEV antibodies in mouse sera. A good correlation was observed between the functional and binding titers in mouse sera determined using two different methods. This result supports the continued use of the enzyme-linked immunosorbent assay as the primary serological assay assuming that the coating antigen contains conformational and native-like epitopes, as in the case for HEV p239.